Terrorism: an international perspective - Martin, Gus (SAGE, 2019)
A comprehensive investigation of modern terrorism and the global terrorist environment, topics discussed include the Causes of Terrorism, the Role of the Media, Cyberterrorism, Religious Terrorism, and The Future of Terrorism.